Biomedical research's unpaid debt. (20th March 2014) - Thompson, Winston E; Pattillo, Roland A; Stiles, Jonathan K; Schatten, Gerald
<x xml:space="preserve">Abstract</x> African Americans suffered exploitation and discrimination in biomedical research long after the abolition of slavery and still face inequalities in research today. The NIH has begun to redress these historical and present‐day injustices. <boxed-text content-type="graphic" id="embr201338274-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>